MODAL SOSIAL DALAM KOMUNITAS NELAYAN SEBAGAI UPAYA MENGHADAPI PENURUNAN HASIL TANGKAP IKAN DAN PERUBAHAN IKLIM - Desi Putri Desi putri; Lesti Heriyanti (Jurnal Analisa Sosiologi, 2024)
The phenomenon of climate change is caused by increasing global warming, which affects the length of the dry season, melting polar ice caps and rising sea levels. Fishing communities rely on marine resources to fulfill various livelihood needs. However, this situation is disrupted due to climate change. This research aims to analyze the role of social capital in helping traditional fishermen in Pasar Bengkulu Village overcome the decline in fish catch due to climate change. The method used to analyze this problem will use a qualitative method. Data collection techniques include observation and interviews. The informants in this research are the fishermen community, especially in the Bengkulu market area. Determination of research subjects was done through the snowball method. The results revealed that the impact of climate change causes fishing communities to experience socio-economic problems. The impact of climate change hampers the fishing community in fulfilling their livelihood needs and makes them vulnerable to poverty. From the social side, fishermen are unable to determine the season due to erratic weather, and the longer distance traveled to catch fish, causing large costs for the community.